2015
DOI: 10.1002/pssa.201532661
|View full text |Cite
|
Sign up to set email alerts
|

Optical vortex pulse illumination to create chiral monocrystalline silicon nanostructures

Abstract: We discovered that a nanosecond optical vortex pulse can create a chiral cone‐shaped monocrystalline silicon (Si) nanostructure (chiral Si nanocone) by transferring its optical angular momentum to a monocrystalline Si substrate. The fabricated Si nanocone, with a length of 4.8 µm and a tip curvature of ∼110 nm, was fully monocrystalline, and it had a spiral structure with an 86 nm line width on a conical surface. Furthermore, its chirality was also determined directly from the handedness of the optical vortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…2 b showing an unclear twisted structure. These results roughly correspond with the previous report 14 . We measured the height of the twisted cone structure using atomic force microscopy (AFM).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…2 b showing an unclear twisted structure. These results roughly correspond with the previous report 14 . We measured the height of the twisted cone structure using atomic force microscopy (AFM).…”
Section: Resultssupporting
confidence: 94%
“…In addition, Si microdroplet ejection perpendicular to a bulk Si target surface using an optical vortex beam with a doughnut profile has been reported 11,12 , and its mechanism is probably based on laser-driven pressure. Furthermore, in an interesting result, the creation of twisted structures has been reported, corresponding with the total angular momentum of the optical vortex 13,14 . As a twisting force will enhance straight ejection of droplets by the gyro effect, an optical vortex beam is expected to offer a well-controlled fabrication technique for microparticles.…”
mentioning
confidence: 91%
“…In general, an ultrafast laser pulse induces the recrystallized silicon to form polycrystalline structures . Such microsecond scale motion of the melted silicon in the optical vortex pulse illumination results in the high crystallinity of the silicon needle, which is identified by the electron diffraction analyses . The OAM should provide a spin on the melted silicon, resulting in the efficient accumulation of the melted silicon in the dark core forming the needle on the substrate.…”
Section: Helical Structuresmentioning
confidence: 99%
“…In this area of original physical demonstrations, recent studies have shown that irradiation by such an OAM field can twist materials, such as metal, silicon, azo‐polymer, and even a liquid‐phase resin with the help of spin angular momentum (SAM) of circularly polarized light with the rotating electric field. This can thus shape helical nano/microstructures …”
Section: Introductionmentioning
confidence: 99%
“…They have potential applications in a variety of research areas, such as optical trapping and manipulation1314, terabit high-speed optical communications1516, and chiral or achiral nanostructure fabrication1718192021. Laguerre-Gaussian (LG) modes, which are eigen modes of the para-axial electromagnetic equation in cylindrical coordinates, are well known as conventional optical vortices.…”
mentioning
confidence: 99%